REALITA PERSIDANGAN TERHADAP WARGA NEGARA ASING YANG MELAKUKAN TINDAK PIDANA DI WILAYAH PENGADILAN NEGERI DENPASAR - Ni Nyoman Metta Yuliarini; Ni Luh Citra Wati; Ni Komang Ratih Kumala Dewi; Lis Julianti; Ni Luh Gede Yogi Arthani (Jurnal Yusthima, 2026)
This research will be conducted for 1 year, the objectives of the research are: 1. To analyze the law enforcement mechanism against Foreign Citizens who commit crimes in the Denpasar District Court 2. To form a concept to strengthen the existence of law through the trial process amidst the increasing number of crimes committed by foreign citizens 3. To explain the benefits and understanding and benefits to the public through published scientific articles regarding the Consistency of Trials in Law Enforcement for Foreign Citizen Defendants in the Denpasar District Court. This research is designed with a qualitative approach. A qualitative approach is research that highlights those related to 1) the factors causing criminal acts committed by foreign citizens in the Denpasar District Court, 2) the extent to which the trial is consistent in law enforcement against foreign citizen defendants in the Denpasar District Court, and 3) the implications of trial consistency on the principle of legal certainty and justice for Foreign Citizen Defendants in the Denpasar District Court. The research was conducted at the Denpasar District Court by taking samples in the jurisdiction of the Denpasar District Court. This research was designed with a qualitative approach. The subjects of the research were Judges who handled cases of foreign citizens in the Denpasar District Court. In this study, the data collection techniques used were (1) in-depth interviews. Informants were selected purposively, specifically within the jurisdiction of the Denpasar District Court and law enforcement officers handling criminal cases against foreign nationals. (3) Observations of developments in law enforcement against foreign nationals. (4) and documentation studies.